Pediatric Resident Perception and Participation in End-of-Life Care. (November 2020) - Niehaus, Jason Z.; Palmer, Megan; LaPradd, Michelle; Haskamp, Amy; Hatton, Amy; Scanlon, Caitlin; Hill, Adam B.
Background: Despite advances in medical care, pediatric deaths are still an unfortunate reality. Most of these deaths occur within a hospital setting. End-of-life care is an important part of medical care for children with serious illnesses. Despite the importance, pediatric providers report a lack of comfort surrounding end-of-life care. Objective: To assess categorical pediatric residents' perceptions and participation in providing end-of-life care to dying children and their families. Study Design: This is a survey-based, descriptive, mixed-methods study. Survey was sent to categorical pediatric residents at Indiana University School of Medicine in June 2018 to obtain both quantitative and qualitative information on resident perception and participation in end-of-life care. Surveys were sent to 100 residents with a response rate of 68%. Setting/Participants: Pediatric residents at Indiana University School of Medicine. Results: The comfort and participation in end-of-life care are limited in all levels of pediatric training. Residents do not feel comfortable with 19 of 22 questions related to end-of-life care. Only 32% of residents felt their education prepared them to participate in end-of-life care. Almost one-fifth (19.5%) of residents report participating in zero aspect of end-of-life care. Themes discussed by residents include education, experience, communication, social norms, emotions, self-care, comfort, and family. Conclusion: More formalized education and training is needed to increase resident comfort with and participation in end-of-life care. Such future interventions should focus on communication surrounding difficult conversations and providing guidance for families.